2019
DOI: 10.1021/acssuschemeng.9b04669
|View full text |Cite
|
Sign up to set email alerts
|

High-Voltage Pulsed Electric Field Preprocessing Enhances Extraction of Starch, Proteins, and Ash from Marine Macroalgae Ulva ohnoi

Abstract: Marine macroalgae are an attractive source for biorefineries as an alternative to terrestrial crops, and new, sustainable macroalgae biomass fractionation methods are needed. One of the least investigated macroalgae-derived products is starch. In this work, we report on a device and a protocol for pretreatment for starch extraction from a green macroalga Ulva ohnoi (U. ohnoi) with an emerging, nonthermal, and environmental friendly technologypulsed electric field (PEF). Using the custom-made insulated gate bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(27 citation statements)
references
References 51 publications
(148 reference statements)
2
25
0
Order By: Relevance
“…[17][18][19][20][21][22]. Furthermore, PEF has been defined as a green extraction technology because of its substantial minimization of toxic solvents, reduction of waste products, and lower energy consumption compared to conventional thermal extraction and dehydration processes [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22]. Furthermore, PEF has been defined as a green extraction technology because of its substantial minimization of toxic solvents, reduction of waste products, and lower energy consumption compared to conventional thermal extraction and dehydration processes [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…doubled when using alkaline solvents (pH 8) compared to water; however, the recovery of proteins from the biomass was still low compared to other physical extraction procedures, such as UAE [ 19 ]. PEF has been described as a promising method for the extraction of proteins from the macroalga Ulva ohnoi [ 20 ]. The authors achieved a 3-fold increase in the yield of proteins from U. ohnoi of with the application of PEF.…”
Section: Process Of Generation and Isolation Of Bioactive Peptidesmentioning
confidence: 99%
“…Another study reported the application of PEF with a custom‐made insulated gate bipolar transistor‐pulsed generator coupled with a gravitation press‐electrode to aid protein extraction from U. ohnoi [45]. Under optimized conditions (see Table 2), a significant enhancement in protein yield, i.e., from 3.16 to 14.94% in the control extract and the extract obtained following PEF treatment, respectively, was achieved [45].…”
Section: Extraction Of Proteins From Macroalgaementioning
confidence: 99%